A Factor-Structural Analysis of the A-K 5D Hikmah Model Based on Data from Islamic Private School Teachers in Narathiwat, Thailand - Witthayanukun, Faison; Cheming, Hartinee; Khiati, Mansour; Yahya Al-Hidabi, Dawood Abdulmalek (IIUM Journal of Educational Studies, 2026)
This cross-sectional survey examined the perceptions of Islamic school teachers in Narathiwat, Thailand, regarding the A-K 5D Hikmah Model and explored its underlying factor structure. Data were collected using a self-administered questionnaire from a sample of 350 Islamic private school teachers selected through stratified random sampling to ensure proportional representation of schools across four size categories (small, medium, large, and largest) based on student population. The research instrument consisted of 35 Likert-scale items adapted from Al-Hidabi and Khiati (2021) to measure the dimensions of the A-K 5D Hikmah Model. Data was analyzed using descriptive statistics to assess teachers’ perceptions of the model and exploratory factor analysis (EFA) to extract the model’s underlying structure. The EFA results revealed five underlying factors—Knowledge and Understanding, Action, Reflective Thinking, Empathy, and Ethical Self-Regulation—with 26 items retained from the original scale. In addition, the overall mean scores indicated high levels of agreement among teachers toward the wisdom dimensions of the model. The results suggest that the A-K 5D Hikmah Model is a valid multidimensional framework for understanding wisdom among Islamic private school teachers. Therefore, it is recommended that school administrators and teachers integrate wisdom-based programs into curricula and instructional practices to enhance holistic teacher development and classroom practice.